Toxicity of Senecio vernalis to laying hens and evaluation of residues in eggs - Eröksüz, H; Eröksüz, Y; Özer, H; Yaman, I; Tosun, F; Kizilay, ÇA; Tamer, U (Comparative Toxicology Lab, 2003)
Diets with 0.0, 0.5, 2.0, or 4.0% ground-aerial parts of Senecio vernalis were fed to groups of 10 laying hens for 210 d. Plant alkaloid content was 0.14% with 8.57% in the basic form and 91.43% in the N-oxide form. Specific alkaloids were senecionin (66.65%), senecivernin (10.37%), seneciphylline (8.51%), integerrimine (8.44%), retrorsine (3.03%), senkirkine (2.35%) and hydroxysenkirkine (0.65%). At the end of the feeding period, no mortality or clinical signs occurred in any test group. However, decreases in egg production, feed efficiency, feed intake and body weight occurred on diets containing 2 or 4% of the plant. Serum gamma-GT was significant elevated and serum albumin and protein were significant decreased in hens fed the 2 and 4% diets. Total bilirubin was significant higher in the 4% group. No free pyrrolizidine alkaloids were detected in eggs indicating that at these rates of dietary exposure, they did not produce residues at the level of detection or that they were bound irreversibly to egg proteins. Hens fed 2 or 4% plant diets had mild to moderate chronic liver changes of periportal or septal fibrosis, megalocytosis, bile duct hyperplasia and early regenerative nodule formation.
Keywords: Pyrrolizidine Alkaloids